Single-cell RNA-seq uncovers lineage-specific regulatory alterations of fibroblasts and endothelial cells in ligamentum flavum hypertrophy - Chen, Yongxin; Zhang, Jue; Feng, Xincheng; Ma, Qinghong; Sun, Chao (Frontiers in Immunology, 2025)
BackgroundLumbar spinal stenosis (LSS) represents a major global healthcare burden resulting in back pain and disorders of the limbs among the elderly population. The hypertrophy of ligamentum flavum (HLF), marked by fibrosis and inflammation, significantly contributes to LSS. Fibroblasts and endothelial cells are two important cells in the pathological process of ligamentum flavum (LF) fibrosis and inflammation. These two cells exhibit heterogeneity in various fibrotic diseases, yet their heterogeneity in LF fibrosis remains poorly defined.MethodsUsing single-cell RNA-seq, we examined the alterations of fibroblasts, endothelial cells, and key genes in the hypertrophic LF, aiming to establish a comprehensive single-cell atlas of LF to identify high-priority targets for pharmaceutical treatment of LSS.ResultsHere, we find there are five distinct subpopulations of LF fibroblasts: secretory-papillary, secretory-reticular, mesenchymal, pro-inflammatory, and unknown. Importantly, in HLF, the proportion of mesenchymal fibroblast subpopulations increases significantly compared to normal LF (NLF), reflecting their close association with the pathogenesis of HLF. Furthermore, critical target genes that might be involved in HLF and fibrosis, such as MGP, ASPN, OGN, LUM, and CTSK, are identified. In addition, we also investigate the heterogeneity of endothelial cells and highlight the critical role of AECs subpopulation in LF fibrosis.ConclusionThis study will contribute to our understanding of the pathogenesis of HLF and offer possible targets for the treatment of fibrotic diseases.